Molecular epidemiology of New Delhi metallo-β-lactamase-producing Escherichia coli in retail market chickens, Shandong, China - Ma, Jing-Xian; Bai, Shuan-Cheng; Xu, Jia-Qi; He, Zhao-Qing; Qi, Yu-Xiang; Wang, Jia-xin; Shi, Yu-Xia; Li, Yu-Bao; Wang, Min-Ge (Frontiers in Microbiology, 2025)
BackgroundThe global spread of carbapenem-resistant Escherichia coli is a major public health concern. An investigation of their presence in the human and food chain products would facilitate the elucidation of the route of their food-borne transmission. Thus, the aim of this study was to investigate the prevalence of NDM-positive E. coli isolates in chicken at retail markets in Shandong, China.MethodsA total of 60 NDM-positive isolates were recovered from 531 E. coli isolates obtained from chickens at the retail market in Shandong. Antimicrobial susceptibility testing and polymerase chain reaction screening were performed to investigate the phenotype and genotype of carbapenemase resistance. Genomic characteristics of the -producing isolates were determined by WGS and bioinformatic analysis.ResultsAll of these isolates were multidrug-resistant (MDR), with a majority exhibiting resistance to meropenem, ampicillin, ceftazidime, cefotaxime, florfenicol, sulfamethoxazole/trimethoprim, and tetracycline. Whole genome sequencing (WGS) analysis indicated that these isolates were belonged to 18 distinct sequence types (STs), with the most prevalent STs being ST515 (17/60) and ST69 (11/60). Additionally, WGS analysis revealed that clonal spread of NDM-positive ST69 and ST515 E. coli isolates at markets in different cities in Shandong. Phylogenomic analysis showed that NDM-positive E. coli isolates from chickens were closely related to those of human origin.ConclusionThis study provides a new insight into the spread of NDM-positive E. coli isolates from retail chicken, and offers essential data for public health management.